Controversy in Deprivation of Citizenship on Charges of Terrorism and Separatism - DEREVYANKO, Bogdan; ZOZULYA, Evgeniy (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
The manuscript deals with the issues of reasonability of involuntary loss of citizenship of Ukraine and presentation of conclusions to the public, including politicians and legislators. Research was conducted using normative, sociological approaches, methods of induction and deduction, analysis and synthesis, comparison and contrast to compare the penalty of deprivation of citizenship (allegiance) in modern world with the exile from tribe at the time of primitive society and from the state in ancient times; the manuscript provides a list of benefits and privileges (with focus on civil, political, social, economic, humanitarian rights and freedoms) of the citizens of Ukraine, which, accordingly, may be lost in the event of involuntary loss of citizenship of terrorism and separatism suspects. Such measure would have a serious effect of punishment if the state guaranteed fundamental rights and freedoms of citizens of Ukraine to the extent defined by internationally recognized standards, significant economic benefits for the citizens of Ukraine, or inability to obtain citizenship of another state. Conclusion was made about the inexpediency of introduction of such penalties at the current stage of development of the economy and civil society in Ukraine.